2018
DOI: 10.1111/ens.12303
|View full text |Cite
|
Sign up to set email alerts
|

Food web structure of aphids and their parasitoids in Belgian fruit agroecosystems

Abstract: Quantitative food webs were constructed between aphids and their parasitoids on fruit crop plants, non‐crop woody and shrub plants, and non‐crop herbaceous plants in fruit agroecosystems of eastern Belgium. The results show that trophic indirect interactions through parasitoids, that is, apparent competition, may govern aphid populations in fruit crop habitats with various non‐crop plants, implying the importance for landscape management and biological control of aphid pests in fruit agroecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Our study found that a wide array of primary parasitoids associated with M. persicae were present in P. persica orchards. The prevalence of this array of parasitoids should make the ecosystem more stable and resilient to potential invasions of new aphid species [3,20,36]. Aphidius matricariae accounted for over 90% of all our primary parasitoids, suggesting that it should be the key parasitoid species considered as a biological control agent in conservation biological control programs and, probably the best candidate for augmentative releases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that a wide array of primary parasitoids associated with M. persicae were present in P. persica orchards. The prevalence of this array of parasitoids should make the ecosystem more stable and resilient to potential invasions of new aphid species [3,20,36]. Aphidius matricariae accounted for over 90% of all our primary parasitoids, suggesting that it should be the key parasitoid species considered as a biological control agent in conservation biological control programs and, probably the best candidate for augmentative releases.…”
Section: Discussionmentioning
confidence: 99%
“…Within Europe, Spain is a leading producer and accounts for more than 30% of total European production [1], and most of Spain’s peach orchards are concentrated in the Catalonia region in northeastern Spain [2]. Ten aphid species have been reported to infest European peach trees [3,4], with the green peach aphid, Myzus persicae (Sulzer) and species of the Hyalopterus genus being the most serious pests. Peach trees are the primary host for both aphids and are necessary for their survival [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…From agricultural fields, fruit orchards containing primary (PHP; fruit trees) and secondary host plants (SHP; herbaceous plants) can provide significant data on the interactions of aphids with heteroecious life cycles, which migrate between different host plants during the year. As an example of this, Alhmedi et al (2018) reported that non-crop plants (herbaceous or woody plants) showed a significant richness compared to fruit crop plants in terms of many biodiversity values, especially the species richness of both aphids and parasitoids.…”
Section: Introductionmentioning
confidence: 99%
“…The subfamily is represented by more than 500 species belonging to 38 genera, about half of which belong to the group of strict specialists which attack only one aphid species, and most of them are distributed in the Holarctic region (Žikić et al ., 2017). Furthermore, Aphidiinae parasitoids are important agents used in the biological control of aphid pests, and have a rich biodiversity in orchards (Carroll and Hoyt, 1986; Monteiro et al ., 2004; Kavallieratos et al ., 2008; Rakhshani, 2012; Alhmedi et al ., 2018; Aparicio et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation